CLIL teachers’ materials: Sciencetextbook’s evaluative template - Codina-Fernández, Judit (My University, 2019)
The textbook is an object which is present in almost all classrooms. Moreover, in the majority of cases, it is the basis of the student’s learning process. Teachers spent most of the time in class using the textbook, which provides them with guidance, activity design and multiple resources Although disadvantages can be found in the textbooks’ usage, it is certain that they are still used a lot in teaching, mostly in subjects in which the language used is not the students’ mother tongue, as it is the case in bilingual education. For this reason and in terms of CLIL methodology, a textbook evaluation process is needed in order to better attain the CLIL fundamentals, the learning goals and the target group needs. Bearing the aforementioned reasons in mind, this study’s main objective is to create a CLIL Science evaluation template to attend one of the reasons mentioned above: the CLIL fundamentals. Therefore, the present study’s template lays its basis on Coyle’s 4C’s framework and the main features this theory implies (the Language Triptych, Bloom’s taxonomy, BICS and CALP, intercultural awareness…). Moreover, in order to attain the main objective, an analysis among three CLIL textbooks evaluation template is carried out in this study. Besides, the final template is applied to three different CLIL Science textbooks from 3rd grade level aiming to validate the template. In consequence of the fact that textbooks’ usage often relies on teachers’ own teaching manner and objectives, the final template aims to be a useful tool to analyse and evaluate CLIL Science textbook focusing on the 4C’s framework in order to choose the most effective one or to better know its strengths and weaknesses.
Keywords: textbook; CLIL; 4C’s framework; evaluation template; Máster Universitario en Educación Bilingüe